Colloborative learning in multicultural classrooms : a case study of Dutch senior secondary vocational education - Tielman, Kennedy [Verfasser]; den Brok, Perry [Verfasser]; Bolhuis, Sanneke [Verfasser]; Vallejo, Bertha [Verfasser] (My University, 2012)
"This research presents a descriptive study regarding collaborative learning in a multicultural classroom at a vocational education school in The Netherlands. The study bridges two domains of research: research on culturally diverse learning environments – which has mostly concerned primary and general secondary education – and studies on collaborative learning. It analyzes current practices and perceptions of both teachers and students applying collaborative learning in a culturally diverse, competence-based learning environment. The results suggest that in a multicultural classroom, students, on the one hand, are mostly focused on their individual performance, resulting in poor collaboration among classmates. On the other hand, teachers seem unaware of their own role in affecting students’ behavior and the influence of the cultural backgrounds of students on collaborative learning processes." (Autorenreferat, BIBB-Doku)
Keywords: S 3.1.2.1 Berufliche Teilzeitschulen, Berufsschulen; L 2.2 Didaktik; L 3.3 Lehrer-Lerner-Interaktion; I 2.2.1 Westeuropa; Berufsschule; Unterricht; Kooperatives Lernen; Heterogenität; Multikulturalität; Kompetenzorientierung; Lehrer-Schüler-Beziehung; Niederlande